Pengembangan Kurikulum Ditinjau Dari Tingkat Kabupaten Sambas Pada Daerah Tertinggal di madrasah Ibtidaiyah Kabupaten Sambas Provinsi Kalimantan Timur - Aslan, Aslan (MADINAH, 2016)
Education held in every educational unit, from basic education to higher education, even conducted in informal and informal institutions should be the foundation for the personal formation of learners, and society at large. However, in reality the quality of education, especially the quality of education output is still low when compared with the quality of education output in other countries, both in Asia and in ASEAN region. The low quality of education requires a thorough handling, because in the life of a nation, education plays a very important role to ensure the survival of the State and the nation, is also a vehicle for improving and developing the quality of human resources. (Mulyasa, 2013: 13). So with that, to improve the quality of Human Resources can not be separated from the curriculum in the education process they experienced. The curriculum we want today is not an ever-changing curriculum that ends up just like that. But more important is how to improve student learning outcomes, student behavior that leads to the positive side rather than towards the negative. So with that, it can not be doubted, that professional competence of teachers is expected in developing plans pelaksaaan learning and syllabus used in learning. Especially now, the government program in the 2013 curriculum needs to be implemented in schools in Indonesia this. And it is also undeniable that the 2013 curriculum is not suitable for the Level II region or known by the Regency and in the area of ​​the district that there is a lagging and underdeveloped areas that lack of media in delivering the 2013 curriculum. Thus, in the case of local content in Madrasah Ibtidaiyah, it is necessary for a teacher, teacher group activities and education offices to prepare a step in the development of the Madrasah Ibtidaiyah level curriculum in Sambas district in the disadvantaged areas in order to create an active, effective and efficient for the achievement of a nation of honorable sambas and ready to compete with ASEAN countries.